2000
DOI: 10.1111/j.1835-2561.2000.tb00066.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Enterprise Resource Planning Systems on Accounting Practice – The Australian Experience

Abstract: 0 ver the past decade, enterprise resource planning (ERP) system offerings from S N , Oracle, Peoplesoft, Baan, JD Edwards and others have become the dominant business information system software platform for large companies and government bodies in Anglo-American countries (Davenport, 1998).' In Australia, for example, a 1998 survey by the GartnerGroup, CFO magazine and the ASCPA found an average ERP usage rate of 52.7%, ranging from a high of 71.4% in manufacturing to a low of 29.6% in "other services" (Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 2 publications
11
96
1
9
Order By: Relevance
“…Hypothesis H1 confirmed that information quality influences accounting practices, in accordance with Booth et al (2000), Granlund and Malmi (2002), Galani et al (2010) and Kanellou and Spathis (2011). One possible explanation for this result proposes that the extended information provided by the AIS would allow companies to diversify their use of accounting practices.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Hypothesis H1 confirmed that information quality influences accounting practices, in accordance with Booth et al (2000), Granlund and Malmi (2002), Galani et al (2010) and Kanellou and Spathis (2011). One possible explanation for this result proposes that the extended information provided by the AIS would allow companies to diversify their use of accounting practices.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, Granlund (2001) identified that the establishment of an advanced information technology would introduce a change in management accounting practices. In the particular case of ERP systems, the latter is considered an important source of new accounting practices (Booth et al, 2000).…”
Section: Impact Of Erp System Quality On the Accounting Practices Usedmentioning
confidence: 99%
“…Notwithstanding these works, few studies exist where a structured approach to the analysis of cost factors in a process-aware information system is undertaken. Since the introduction of ERP systems, a number of studies have been conducted on the effects of ERP systems on traditional management accounting practices [1,7,8]. Recently, Vom Brocke et al proposed an information model to link the ARIS accounting structure with ARIS process semantics using Event Driven Process Chains (EPC) [21].…”
Section: Related Workmentioning
confidence: 99%
“…Based on the employment size classification of SMEs, Table 2 shows a comparison of the survival rates of small, medium and large businesses in Australia between June 2007 and June 2011 [28]. Implementing an ERP system is considered an important strategy for establishing new robust accounting practices for improving the SME survival rate [29]. However, SMEs show resistance to ERP adoption due to the constraints and barriers involved in the domestic and global contexts, and these need to be studied from the perspectives of both ERP consumers, as well as vendors.…”
Section: Usamentioning
confidence: 99%